Utilizing jackfruit seed and dragon fruit peel in swiss rolls: Waste valorization for local culinary tourism development - Enita Rahayu; Maria Veronika Simanjuntak; Praseptia Gardiarini; Firda Rahmayanti (Journal of Rural Tourism, 2026)
Purpose – This study aims to develop a nutritionally enhanced Swiss roll by incorporating jackfruit seeds and dragon fruit peel as locally sourced ingredients, and to position the product as a distinctive Indonesian culinary innovation that could strengthen the attractiveness of local gastronomic tourism. Methodology/Design/Approach – A quantitative approach was applied using a hedonic sensory test involving trained panelists to evaluate product acceptability across several formulations.Findings – The Swiss roll was formulated by integrating jackfruit seed powder into the batter and using dragon fruit peel as the filling. Sensory evaluation results showed aroma acceptability scores of 4.23 for Formula 1 (F1), 4.07 for Formula 2 (F2), and 3.57 for Formula 3 (F3) on a 5-point Likert scale, indicating an overall positive (“like”) response from panelists. F1 demonstrated the highest acceptance level. These findings confirm that the product is well-received and presents a nutritious, locally sourced alternative that has the potential to enhance the diversity and appeal of Indonesian culinary tourism.Originality/Value – This study highlights the valorization of food by-products in pastry innovation, demonstrating how jackfruit seeds and dragon fruit peel can be transformed into a marketable gastronomic product. The approach contributes to sustainable local food development while adding value to regional tourism offerings.